Estilos de liderazgo existentes versus los ideales en los directivos de la cámara de comercio del Amazonas y propuesta estratégica para el fortalecimiento organizacional (2021)
The objective of this descriptive research study was to evaluate the existing leadership styles versus the ideals of the directors of the Amazon Chamber of Commerce. This was done in order to create a strategic proposal to strengthen the organization. The mixed methods research approach was used, utilizing qualitative tools such as document inspection and data triangulation as well as the application of an administrative compliance grid as a quantitative tool for self-evaluation, co-evaluation, and evaluationby five officials from the managerial level and eight from the care and auxiliary level. The results indicated that the 5.5 leadership style was the most common. Midway management represented an opportunity forthe improvement of the entity since there is a balanced management at the labor level and in the well-being of the people. These two variables were unable to be raised to a higher level of ideal state in order to achieve the organizational success.